SIMULATION RESEARCH ON GEAR CRACK FAULT BASED ON ADAMS - ZHANG YongXiang; TU Hu; LU Jie; ZHU DanChen; ZHAO Lei (Jixie qiangdu)
In order to study the variation law of gear crack fault vibration signal under different conditions,the gear crack fault was simulated based on the characteristic of flexible body in ADAMS,and the fully flexible gearbox models with different degrees of gear crack fault were established.Crack depth,position of measuring points,input speed and load torque were analyzed on their effects to vibration signal of the gearbox.The results show that the deeper the crack,the closer the position of the measuring point to the crack failure source,the larger the input speed and load torque,the greater the impact and amplitude of the vibration signal,and the amplitude of the vertical acceleration signal is larger than that of the axial acceleration signal.The analysis results of the transmission characteristics of the system show that the transmission law and frequency distribution of the vibration signal are basically consistent with the results of the variation law of vibration signal of different measuring points,and the simulation results are verified by hammering experiments.The research results have a certain reference value for the simulation and experimental research of gear crack fault.